Chronic lower-dose relaxin administration protects from arrhythmia in experimental myocardial infarction due to anti-inflammatory and anti-fibrotic properties. (1st January 2018) - Beiert, Thomas; Knappe, Vincent; Tiyerili, Vedat; Stöckigt, Florian; Effelsberg, Verena; Linhart, Markus; Steinmetz, Martin; Klein, Sabine; Schierwagen, Robert; Trebicka, Jonel; Roell, Wilhelm; Nickenig, Georg; et al.
Abstract: Background: The peptide hormone relaxin-2 (RLX) exerts beneficial effects during myocardial ischemia, but functional data on lower-dose RLX in myocardial infarction (MI) is lacking. Therefore, we investigated the impact of 75 μg/kg/d RLX treatment on electrical vulnerability and left ventricular function in a mouse model of MI. Methods and results: Standardized cryoinfarction of the left anterior ventricular wall was performed in mice. A two week treatment period with vehicle or RLX via subcutaneously implanted osmotic minipumps was started immediately after MI. The relaxin receptor RXFP1 was expressed on ventricular/atrial cardiomyocytes, myofibroblasts, macrophages and endothelial but not vascular smooth muscle cells of small coronary vessels. RLX treatment resulted in a significant reduction of ventricular tachycardia inducibility (vehicle: 91%, RLX: 18%, p  < 0.0001) and increased epicardial conduction velocity in the left ventricle and borderzone. Furthermore, left ventricular function following MI was improved in RLX treated mice (left ventricular ejection fraction; vehicle: 41.1 ± 1.9%, RLX: 50.5 ± 3.5%, p  = 0.04). Interestingly, scar formation was attenuated by RLX with decreased transcript expression of connective tissue growth factor. Transcript levels of the pro-inflammatory cytokines interleukin-6 and interleukin-1β were upregulated in hearts of vehicle treated animals compared to mice without MI. Application of RLX attenuated this inflammatory response. In addition, macrophage infiltration was reduced in the borderzone of RLX treated mice. Conclusion: Treatment with lower-dose RLX in mice prevents post-infarction ventricular tachycardia due to attenuation of scar formation and cardiac inflammation. Therefore, RLX could be evaluated as new therapeutic option in the treatment of MI.